Penerapan mesin pemeras sari Nenas dan pengaduk dodol Nenas untuk meningkatkan produktivitas dan kualitas produk pada Kelompok Masyarakat Nenas Berduri (PONARI) - Retno Tri Wahyuni; Elva Susianti; Rika Perdana Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The potential for developing of Pineapple processed food industry in Kampar is very large when viewed from the availability of raw materials and regional potential. Kampar is a tourist destination therefore the souvenir industry is very prospective. Efforts to increase the added value of pineapples are mostly done through pineapple agroindustry. Pokmas Nenas Berduri (PONARI) is one of the community groups in Kampar Regency that runs pineapple agroindustry with favorite product are pineapple syrup and dodol. In running of its business, PONARI has problems in the field of production, namely the availability of unhygienic pineapple juice squeezers and energy and time constraints in the pineapple dodol production process. Based on these problems, a solution was given in the form of applying a pineapple juicer machine and an automatic mixer. From the test results both machines have been functioning properly. The production capacity was 6 kg for the pineapple juicer machine and 5 kg for the mixer machine. The application of the pineapple juicer machine did not cause an increase in production costs, while the automatic dodol mixer machine generated electricity costs, causing an increase in production costs for dodol was Rp. 50,-/package.